2005
DOI: 10.1111/j.1365-2222.2005.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Female mice are more susceptible to the development of allergic airway inflammation than male mice

Abstract: Female mice develop a more pronounced type of allergic airway inflammation than male mice after OVA challenge. The reduced percentage of regulatory T cells in the lungs of female PBS-mice may indicate that the level of these cells in the lung during the sensitization phase is important for the development and/or progression of an allergic immune response after multiple OVA challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
167
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(194 citation statements)
references
References 33 publications
19
167
2
4
Order By: Relevance
“…Receptors for sex steroids have been identified on lymphocytes, monocytes and mast cells (26,27). A recent study tested the hypothesis that female mice are more susceptible to the development of allergic asthma than male mice and studied allergic immune responses in the lung (28). The results demonstrated that female mice developed a more pronounced type of allergic airway inflammation than male mice after ovalbumin aerosol challenge.…”
Section: Sex Differences and Food Allergymentioning
confidence: 91%
“…Receptors for sex steroids have been identified on lymphocytes, monocytes and mast cells (26,27). A recent study tested the hypothesis that female mice are more susceptible to the development of allergic asthma than male mice and studied allergic immune responses in the lung (28). The results demonstrated that female mice developed a more pronounced type of allergic airway inflammation than male mice after ovalbumin aerosol challenge.…”
Section: Sex Differences and Food Allergymentioning
confidence: 91%
“…In particular, total lung capacity and enhanced pause (Penh) responses to methacholine aerosol have been reported to differ in naĂŻve male and female mice (19,22,24). Importantly, we recently observed a considerable sex difference in murine airway responsiveness to cholinergic stimulation, as assessed by invasive measurement of respiratory mechanics, wherein the airways of naĂŻve male C57BL/6 and BALB/c mice were found to be considerably more sensitive to methacholine aerosol than were those of naĂŻve females (4).…”
mentioning
confidence: 83%
“…3 Thus, we found a protective effect in a mouse model associated with higher risk of atopy in humans.…”
mentioning
confidence: 57%
“…2 University Nice Sophia-Antipolis, EA6302 Immune Tolerance Team (TIM), Nice, France and 3 The International Inflammation 'in-FLAME' Network, Worldwide Universities Network. Correspondence: V Verhasselt (verhasselt@unice.fr)…”
mentioning
confidence: 99%